Simultaneous co-saccharification and fermentation of sago hampas for bioethanol production - Empina, Jabang (Universiti Malaysia Sarawak (UNIMAS), 2013)
Abundance of lignocellulosic biomass provides a good solution to the demands of energy crops in producing biofuel like biodiesel and bioethanol. In this study, bioethanol was produced via the Simultaneous coSaccharification and Fermentation (Sc-SF) process. The processing steps in Sc-SF were virtually the same as in Simultaneous Saccharification and Fermentation (SSF), except for the addition of two enzymes for saccharification. Amylase and cellulase were added for co-saccharification of sago starch residue and sago fibre. Then, Saccharomyces cerevisiae was used to ferment the hydrolysates. Samples were analysed using High Performance Liquid Chromatoghrphy (HPLC). Sc-SF showed high yields of hydrolysis and ethanol production within the first 6 hours of fermentation. Glucose production was 37.86 gil for 5.0% sago hampas and 17.47 gil for 2.5% sago hampas. The highest bioethanol yield in 5.0% sago hampas was 80.50%. Meanwhile, the highest bioethanol yield in 2.5% sago hampas was 73.19%. This study indicated that there is feasibility of increasing bioethanol production via Sc-SF.